Penguatan Kebikjasanaan Imigrasi Dalam Pencegahan Tindak Pidana Penyelundupan Manusia Lintas Negara - Adi Papa Jefrianto Bondi; Emanuel Brianto Aradoni; Yohanes Arman (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The position of Indonesia's territory which has various kinds of diversity and breadth of geography that is surrounded by waters makes various kinds of vulnerabilities occur in state security. Suryo Sakti Hadiwijoyo explained that the security characteristics that occur due to a strategic position and having sea borders with international trade routes will have an impact on regional security and defense. The research method used by the author in this study is a qualitative method. Qualitative research method is. research that intends to understand phenomena about what is experienced by research subjects such as behavior, perceptions, motivations, and actions holistically (whole) and by means of descriptions in the form of words and language in a special natural context by utilizing various natural methods. Optimizing the Role of Border Policy and Law in Enforcement of Human Smuggling Crimes Human Smuggling or People Smuggling has the meaning and definition of seeking to obtain a financial or other material advantage by crossing borders between countries without using legal methods, Strengthening Community-Based Management In terms of supervising cross-border criminal acts, especially in human smuggling. Basically transnational or cross-country criminal acts that occur are routes of mass movement from one country to another, which occur on a large scale and are increasingly not being recovered and then giving rise to illegal migration without immigration documents in accordance with existing regulations. . The existence of advances in communication technology that makes it easier for everyone to form a community relationship between nations, between communities and between individuals so as to create borderless. In carrying out supervision and prosecution of transnational crimes, especially people smuggling, an extra role and performance is needed for each stakeholder who has the task of goods and functions, especially in controlling border.